THE TEACHING OF BASKETBALL PASSES AS A HELPER FOR THE FRONT THROW WITH ONE OF THE HANDS (Fiep Bulletin - online, 2014)
The basketball is a collective event with implications that come from the necessity of athletes with a specific body, obliging the professional who works in the beginner's level to work with different methodologies. To get at the game there are several technical fundaments which must be orientated by a secure and consistent way during the initiation level for children, because when he/she gets at the game, it will depend on body actions related to the perfect execution of learned fundaments in the initiation. It was the objective in this project to investigate the application of a sequential protocol of passes, succedaneum to the national literature, giving this way, body experience to the initiation of the front throws with one of the hands. The methodology can be characterized as an experience, and the sample was formed of 17 girls of a public school in the city of Pres. Prudente - SP. To verify the evolution of the teaching, it was realized before and after tests, the ones specific for basketball, as in the passes as in the throw, (Knoux, apud Matheus, 1980), applying the teaching passes and the throw between them. In the statistic treatment it was used the comparison test of two averages for neck and neck data, in the two fundaments, which consists in the difference between the obtainable observations and compared with a critical value based in the t-Student table at the level of meaning á (á = 0,05). The statistic test rejected the hypotheses of averages equality, accepting the difference between the averages at the level of meaning of 5%, in the teaching of passes as in the throw. Hence, the protocol of passes used, succedaneum to the national literature is efficient, as well as, it provides necessary body experience for the teaching of throw. It's concluded that the sequential protocol of passes can serve as a model for teachers who work in the initial phase of basketball, giving also positive transference for the teaching of the front throw with one of the hands.
Keywords: teaching; technical fundaments; Basketball